Exploring Classroom Management Strategies Used by English Teachers in Speaking Classes - Aziza, Nur; Ashadi, Ashadi; Umar, Nasir (International Journal of Contemporary Studies in Education, 2024)
Classroom management continues to be a teacher's struggle for teaching performances because it relates to students learning. There needs to be more understanding and knowledge about managing the students and classrooms with diverse student behaviour to solve the problems, particularly when identifying students' problems and understanding their different characteristics. However, this study explored teacher classroom management strategies in teaching speaking classes, especially in secondary schools. This study aims to (1) explore and describe the classroom management used by English teachers in teaching speaking. (2) find out the teacher strategy used to deal with the students' problems during classroom management's teaching and learning speaking process. (3) examine the impact of classroom management strategy in teaching practice. This study uses semi-structured interviews, observations, and document analysis to collect the data. The data findings reveal that teachers have different ways of dealing with different classroom situations based on their experiences and understanding, especially in speaking classes. Most of them claim to take action on how to respond to students' problems, such as understanding classroom management strategies, organizing, problem-solving, and applying teaching strategies. These strategies have a positive impact on learning engagement in the classroom, such as the students being more interested in learning English lessons, obeying the rules, talking actively, and having motivation.